Association between oxidative balance score and methylation cycle biomarkers in US adults: insights from the national health and nutrition examination survey - Xuna Liu; Yiwen Wang (Frontiers in Nutrition)
BackgroundOxidative stress(OS) is implicated in various diseases, and the methylation cycle plays a critical role in numerous biological processes including DNA methylation and antioxidant defense. We aimed to investigate the relationship between oxidative balance score (OBS) and methylation cycle.Materials and methodsThe study enrolled 28,061 adults ≥20 years old from the NHANES 2003–2014. Methylation cycle biomarkers included serum folate, RBC folate, vitamin B6, vitamin B12, homocysteine (HCY), and methylmalonic acid (MMA). OBS was scored by 20 dietary and lifestyle factors. We employed weighted linear regression and restricted cubic spline (RCS) models to analyze the correlations among OBS, and methylation cycle.ResultsIn a nationally representative cohort of US adults (mean age: 47.04 ± 0.25 years; 51.76% female), OBS demonstrated significant associations with key methylation cycle biomarkers. After adjusting for potential confounders, OBS exhibited a positive association with serum folate, RBC folate, vitamin B6, and vitamin B12, a negative correlation with HCY (all P for trend < 0.001), and no correlation with MMA (P for trend = 0.07). Higher dietary OBS was correlated with increased levels of serum folate, RBC folate, vitamin B6, and vitamin B12, and decreased levels of HCY (all P for trend < 0.001). Similarly, a higher lifestyle OBS corresponded to increased serum folate, vitamin B6, and vitamin B12, as well as decreased HCY (all P for trend < 0.05). Stratified analyses demonstrated that OBS had a strong positive correlation with serum folate, RBC folate, vitamin B6, and vitamin B12, and a strong negative correlation with HCY. Additionally, the negative correlation between OBS and MMA was observed in the elderly population (≥ 60 years old) when stratified by age. RCS regression analysis revealed that with the increase in OBS, serum folate, RBC folate, vitamin B6, and vitamin B12 also increased, while HCY and MMA decreased.ConclusionOur findings demonstrate a significant relationship between OBS and the methylation cycle. Higher OBS is positively associated with folate and vitamins B6/B12, and negatively with HCY.